Home Total Parenteral Nutrition for Intestinal Failure in Patients with Advanced Small Intestinal Neuroendocrine Neoplasms. (18th August 2021) - Liu, Man; Laskaratos, Faidon-Marios; Bennell, Jose; Chen, Jie; Toumpanakis, Christos; Mandair, Dalvinder; Caplin, Martyn
Abstract: The role of total parenteral nutrition (TPN) in cancer patients is controversial, but it may be a treatment option for some patients with indolent but advanced small intestinal neuroendocrine neoplasms (SI-NENs). The aim of this study is to investigate whether home TPN was associated with long-term survival and to assess the indications, duration and complications of TPN in patients with advanced SI-NENs. Patients with advanced SI-NENs who received home TPN were retrospectively included. Electronic records were reviewed for clinical information. Five patients receiving home TPN were identified out of 1011 patients with SI-NENs in our center. The median duration of TPN administration was 12 mo. Small bowel obstruction was the most common reason for TPN initiation. TPN-related complications included two catheter infections, one thrombosis and one episode of TPN-related transaminitis. At the last follow-up, three patients had died and two were alive. The median survival was 12 mo. Overall estimated 1-yr probability of survival on home TPN by Kaplan–Meier analysis was 40%. In conclusion, home TPN may be a treatment option in highly selected advanced SI-NEN patients with severe gastrointestinal tract dysfunction. The initiation of home TPN is associated with long-term survival (≥1 yr), and complication rates appear acceptable.